THE ROLES OF SYARIAH MICRO FINANCE INSTITUTION (LKMS) IN ELIMINATING THE POVERTY IN INDONESIA (CASE STUDY OF BAITUL MAAL WAT TAMWIL) - Syarief Gerald Prasetya (The Accounting Journal of Binaniaga, 2016)
In accordance with BPS data mentioning that the total of poor people in Indonesia in September 2014 had reached 27.73 (10.96%), this total was still quite big eventhough it had been decreasing from time to time eversince. It explains that there are still many people leaving under poverty limitation. The main reason is that they do not have any sufficient financial capital to do their business since most of poor people are UMKM (Small and Middle Business class) people. Therefore BMT (Baitul Maal Wat Tamwil) has appeared to help grass-root people obviously as BMT roles has been able to increase their productivity accordingly. Relating to the total of poor people which had been reducing since 2009 up to September 2014 except in September 2013 it had increased due to the increasing price of the fundamental goods needed by the people refers to the increasing price of BBM (fuel) in June 2013. As a matter of fact, it is getting along with the increasing of BMT Institutions in Indonesia so that the existency of BMT has been the most important roles in elimination of the poverty in Indonesia.Keywords: baitul maal wat tamwil, poverty, micro finance institution.